Short‐Term Impacts of the Megaurbanizations of New Delhi and Los Angeles Between 2000 and 2009. Issue 1 (3rd January 2019) - Jacobson, Mark Z.; Nghiem, Son V.; Sorichetta, Alessandro
Abstract: Urban areas are expanding worldwide due to increasing population, standard of living, and migration from rural areas. This study uses satellite and road data to quantify the urbanization of two megacities, New Delhi and Los Angeles, between 2000 and 2009. It then estimates, with a three‐dimensional nested global‐through‐urban climate, weather, and air pollution model, Gas, Aerosol, Transport, Radiation, General Circulation, Mesoscale, and Ocean Model, the short‐term atmospheric impacts of such urbanization alone. The simulations account for changes in meteorologically driven natural emissions, but not anthropogenic emissions, between 2000 and 2009. New Delhi's urban extent, defined based on the physical existence of its built structures and the transitional gradient from buildings to rural areas rather than on abrupt administrative borders, increased by ~80% and Los Angeles's by ~22.5% between 2000 and 2009. New Delhi experienced a larger increase in its urban extent relative to its population during this period than did Los Angeles. In both megacities, urbanization increased surface roughness, increasing shearing stress and vertical turbulent kinetic energy, decreasing near‐surface and boundary layer wind speed, contributing to higher column pollution levels. Urbanization may also have increased downward solar plus thermal infrared radiation fluxes to the ground and consequently upward latent and sensible heat fluxes from the ground to the air, increasing near‐surface air temperatures. As such, urbanization alone may have had notable impacts on both meteorology and air quality. Plain Language Summary: This study quantifies, with satellite and road data, the changes in urban extent of two megacities between 2000 and 2009. During that period, the urban extent of New Delhi was found to have increased by ~80%, and that of Los Angeles's, by ~22.5%. The study then estimates, with a three‐dimensional model nesting from the globe to each urban area, the short‐term impacts of such urbanization alone. In both megacities, urbanization increased near‐surface air temperatures and decreased wind speeds while increasing vertical turbulence and the column abundance of several pollutants due to the wind stagnation. As such, urbanization may impact both meteorology and air quality notably. Key Points: A new method of quantifying urban extent from satellite data is derived New Delhi and Los Angeles urban extents increased ~80% and ~22.5% from 2000 to 2009 Such changes alone had substantial modeled impacts on short‐term weather and pollution